Analysis of the characteristics of cracked teeth and evaluation of pulp status according to periodontal probing depth - Sung-Eun Yang; A-Ra Jo; Hye-Jin Lee; Sin-Young Kim (BMC, 2017)
Abstract Background The purpose of this study was to analyze the characteristics of cracked teeth and to evaluate pulp status according to periodontal probing depth (PPD). Methods A total of 182 cracked teeth were included. The location and type of the cracked teeth, age and gender of the patients, restoration type, pulp status, PPD, and radiographic findings were analyzed. Results Mandibular second molars (25.3%) were the most frequently involved teeth, followed by mandibular first molars (22.5%), maxillary first molars (22.0%), and maxillary second molars (17.6%). The patient age was most frequently 50-59 years. Cracks occurred mainly in nonbonded restorations, such as gold (26.9%), and were usually found in intact teeth (37.9%). A total of 103 teeth (56.6%) had an initial PPD of less than 3 mm, while 40 (22.0%) had a PPD of 4-6 mm, and 39 (21.4%) had PPD of 7 mm or more. A total of 33 cracked teeth (18.1%) were diagnosed with pulp necrosis, 40 (22.0%) with irreversible pulpitis, and 97 (53.3%) with reversible pulpitis. The incidence of pulp necrosis was 31.8% among cracked teeth with a PPD of 4-6 mm, and 28.6% among those with a PPD of 7 mm or more. Conclusions Cracks occurred mainly in molar teeth, and were commonly found in intact teeth with no restoration. Patients with cracked teeth were most frequently aged 50-59 years. Cracked teeth showing a PPD of more than 4 mm were more likely to show pulp necrosis.